2012
DOI: 10.1371/journal.pone.0043901
|View full text |Cite
|
Sign up to set email alerts
|

Combination Training in Aging Individuals Modifies Functional Connectivity and Cognition, and Is Potentially Affected by Dopamine-Related Genes

Abstract: BackgroundAging is a major co-risk factor in many neurodegenerative diseases. Cognitive enrichment positively affects the structural plasticity of the aging brain. In this study, we evaluated effects of a set of structured multimodal activities (Combination Training; CT) on cognitive performances, functional connectivity, and cortical thickness of a group of healthy elderly individuals. CT lasted six months.MethodologyNeuropsychological and occupational performances were evaluated before and at the end of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 72 publications
(98 reference statements)
2
69
0
Order By: Relevance
“…34 In contrast, elderly individuals carrying the DRD3 Ser/Gly genotype had more benefit from multimodal cognitive training than the carriers of the Ser/Ser genotype. 35 Importantly, preclinical studies suggest that D 3 receptor blockade appears to enhance cognitive function, including memory, attention, learning, processing speed, social Lack of age-dependent change in D 3 availability S Nakajima et al recognition, and executive function (see review by Nakajima et al), while D 3 receptor agonism seems to impair it. 33 D 3 receptor antagonists may exert their pro-cognitive effect by enhancing the release of acetylcholine in the prefrontal cortex, disinhibiting the activity of DA neurons projecting to the nucleus accumbens or prefrontal cortex, or activating CREB signaling in the hippocampus.…”
Section: Resultsmentioning
confidence: 99%
“…34 In contrast, elderly individuals carrying the DRD3 Ser/Gly genotype had more benefit from multimodal cognitive training than the carriers of the Ser/Ser genotype. 35 Importantly, preclinical studies suggest that D 3 receptor blockade appears to enhance cognitive function, including memory, attention, learning, processing speed, social Lack of age-dependent change in D 3 availability S Nakajima et al recognition, and executive function (see review by Nakajima et al), while D 3 receptor agonism seems to impair it. 33 D 3 receptor antagonists may exert their pro-cognitive effect by enhancing the release of acetylcholine in the prefrontal cortex, disinhibiting the activity of DA neurons projecting to the nucleus accumbens or prefrontal cortex, or activating CREB signaling in the hippocampus.…”
Section: Resultsmentioning
confidence: 99%
“…Recent restingstate fMRI studies are largely composed of functional connectivity analyses, which examine the interregional temporal correlation between predefined seed regions and related functional regions. Previous training studies were prone to use functional connectivity methods 10,24,44 , which particularly emphasized the global integration of neural networks by means of indicators reflecting interregional cofluctuations, to examine brain plasticity. The development of available analytical tools for resting-state fMRI data primarily examines integration-related connectivity measures.…”
Section: Discussionmentioning
confidence: 99%
“…Exerciserelated brain alterations include structural changes in the temporal and prefrontal lobes 8 and increased taskrelated activation in the prefrontal cortex 9 . Recent resting-state fMRI studies have demonstrated that cognitive and physical training also changed restingstate functional connectivity 10 . Functional connectivity reflects the temporal coherence of intrinsic brain activity obtained in different brain regions.…”
mentioning
confidence: 99%
“…Although the gene does not seem to influence general cognitive ability or reasoning skill (Ball et al, 1998;Gong et al, 2011), the DRD3 Ser/Ser genotype was linked to greater cognitive flexibility (measured by Wisconsin Card Sorting Test performance) (Lane et al, 2008), and elderly individuals carrying the DRD3 Ser/ Gly genotype benefitted from cognitive training more than those with the Ser/Ser genotype (Pieramico et al, 2012). Even fewer studies have explored the relationship between cognitive function and DRD3 Ser9Gly polymorphisms in individuals with substance use disorders.…”
Section: Evidence That the D 3 Receptor Is Involved In Cognitive Funcmentioning
confidence: 99%